Popeye (Let's Have Healthy Snacks Extension Program) at SDN 17 Gurun Laweh, Nanggalo District in 2022 - Dian Febrida Sari; Nila Eza Fitria; Nurleny Nurleny; Masni Hayati; Eka Putri Primasari; Putri Nelly Syofiah; Masri Rahayu Putri; Gyta Maida Vilosta; Mayyang Santola Rifa; Diana Fitri; Maita Alifa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
SDN 17 Gurun Laweh is one of the schools located in Kampung Koto, Gurun Laweh Village, Nanggalo District, Padang City, does not yet have a school cafeteria, so students snack around the school. Many food vendors use motorbikes that sell around the school such as grilled meatballs, cireng and others. The school could not confirm the cleanliness and health of the snacks. The school's policy regarding snacks that students should not consume at school. The efforts that will be made are (1) To approach the school for cooperation in a healthy snack program for school students. (2) Reactivate the small doctor program. (3) Implementing the POPEYE program (PrOgram PEnyuluhan AYo Jajan SEhat) whose activities include providing education on what healthy snacks are and how to choose healthy snacks so that children can avoid disease. By using age-appropriate game media for school children and also reading fairy tales where we know children really like storytelling activities. So that children can understand the material taught and the achievements to be achieved can be achieved optimally. The targeted outputs are publication of articles in accredited national journals, publications in print and electronic media, increasing partner knowledge about healthy snacks.